Exploring the factors of perfectionism within the Big five personality model among Filipino college students - Navarez, Joel C. (Animo Repository, 2010)
The study dealt with determining if perfectionism through its different scales would have an effect on the five factors of personality. The scales of perfectionism would include Concen1 over Mistakes, Personal Standards, Parental Expectations, Parental Criticis111, Doubt about actions and Organization. The five factors of personality tested include Neuroticism, Extraversion, Openness, Agreeableness and Conscientiousness. The study aimed to better understand the complex set of behaviors and characteristics associated with perfectionism. The study is based on the theory of Pertectionis111 by Frost and the Big Five Factor Theory of Personality. It is a cross-sectional predictive investigation that made use of SEM with bootstrapping on data gathered fro1n 106 college students. The results revealed that the proposed 1nodel showed adequate goodness of fit, as indicated by the low chi-square and discrepancy function values (x2=1180.258, df=589, x2/df=2.004) which is significant at .05 alpha level. The sample represents the 111odel well as shown by acceptable fit indices (CF1 =.531, PCFI =.496, RMSEA =.098).